Pengaruh Store Atmosphere dan Experiential Marketing Terhadap Keputusan Pembelian Di Kopi Daong Pancawati - Achmad Imam Tantowi; Anton Widio Pratomo (Jurnal Ilmiah Manajemen Kesatuan, 2020)
This study aims to find out: (1) How is the influence of Store Atmosphere on purchasing decisions (2) How is the influence of Experiential Marketing on Purchasing Decisions. (3) How is the influence of Store Atmosphere and Experiential Marketing on Purchasing Decisions. The total sample of 140 respondents using the Hair formula. The data used are primary data derived from answers to questionnaires. Data processing using Statistical Package For Social Science (SPSS 25) analysis with multiple regression analysis methods, hypothesis testing, and f test. The results of this study are as follows: (1) Store Atmosphere has a positive and significant effect on purchasing decisions in Daong Pancawati coffee with a multiple regression value of 0.353 and has a significant value of 0,000. (2) Experiential Marketing has a positive and significant effect on purchasing decisions in Daong Pancawati Coffee with a multiple regression value of 0.444 and has a significant value of 0,000. (3) Store Atmosphere and Experiential Marketing have a positive and significant effect on purchasing decisions in Daong coffee with a calculated F value of 108.153 and is greater than the f table of 3.06 and has a significant value of 0,000. Keywords: Store Atmosphere, Experiential Marketing and Purchasing Decisions